A PROFIT SHARING SYSTEM OF HAND LINE FISHERMEN AT HILA VILLAGE CENTRAL MALUKU DISTRICT - Saiful Gazali; Angela Ruban (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2022)
Income of hand line fisherman very dependent on the influence of nature and the existence of a working relationship between boat owners and labor fishermen in fishing operations. This study aims to analyze the profit-sharing and income-sharing system of hand line fishermen at Hila Village, Central Maluku District. Primary data was collected through interviews with 6 fishermen and analyzed using the business income equation and profit sharing system as well as the amount of income earned by fishermen. The results showed that hand line business income of Rp23.093.023/month and the application of the profitsharing system is 1:3 for owner fishermen, boats and 1 crew member. However, the boats's share becomes the property of the owner fisherman, so the owner fisherman gets 2 shares and the crew gets 1 share. The income obtained based on the profit sharing system is the owner of Rp15.393.349/month and the crew of Rp7.697.674/month.